(untitled) (Economic and Political Thought, 2014)
The article presents the situation on the Korean Peninsula from the perspective of the involved superpowers (China, Japan, Russia and the USA) as well as the two Korean states. Signalling historical conditions for the superpowers’ policy towards the Peninsula and demonstrating the diverse interests of particular states, the author tries to present and explain their motivation and makes an attempt to predict future developments. Attention is also drawn to unprecedented interdependence of the involved parties, which makes it difficult to imagine that the most important problems in the region can be solved otherwise than by finding a coordinated standpoint and reaching an agreement. The article emphasises the influence of the Korean states’ policy on the superpowers’ behaviour and the importance of internal factors in both Korean states for the pursuit of efficient solutions stabilising the situation on the Korean Peninsula.